The Sun as Source of Radiation - Rudolf Minder; Martin Wolf; Jean-René Leidner (CHIMIA)
Many research programs in the fields of photochemistry, photoelectricity, and photo-electrochemistry are aiming at processes for solar energy utilization. The sun as source of radiation, however, exhibits some characteristics which are very different from those of artificial light sources usually used in the laboratory. - The scope of this paper is to acquaint the researcher not already familiar with radiation meteorology, with some basic principles andfacts. The most important properties of the sun as a source of radiation are surveyed and the different aspects of radiation and their relationships discussed. The intensity of radiation, an important property, is described with some statistical examples. After some remarks on radiation variability and transients, this account finally looks at the spectral distribution of radiation under different conditions.